Il giro di vite. Essere al bivio di fronte ai doni del tempo e della storia - Maurizio Fabbri (Firenze University Press, 2017)
The article the theme of gift in a complex and globalized society: the author deals with the logic of reciprocity and conviviality, by in political and democratic point of view.